AN EFFECTIVENESS OF LEARNING MANAGEMENT SYSTEMS IN HIGHER EDUCATION: THE DELONE AND MCLEAN-SEM APPROACH - Ivander, Filbert; Yang, Marvello; Melyanto, Melyanto; Saragih, Fry Melda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2025)
Abstract: Information Technology has impacted various sectors, including education. Learning Management Systems (LMS) are designed to facilitate lecturers and students in accessing academic activities such as online learning. This study aims to analyze the effectiveness of Learning Management Systems (LMS) among higher education institutions in Indonesia. This analysis is crucial for assessing the effectiveness of LMS use by universities in Indonesia, enabling investments in LMS to yield optimal results. The study employed the D&M IS Success Model and PLS-SEM to evaluate the relationships between various variables, including system, information, service quality, user satisfaction, and benefits. Simple random sampling was used to collect data from 170 universities in Indonesia. This study employed PLS-SEM to investigate the observed variables, including validity and reliability testing, which involves assessing reliability, convergent validity, and discriminant validity. This current study found that all the hypotheses were accepted with p-values below 0,05. These findings contribute to universities paying attention to aspects of system, information, and service quality in Learning Management Systems (LMS) to improve user satisfaction and create a positive perception of benefits. Therefore, this research yields significant results that contribute to higher education in Indonesia, as well as the advancement of knowledge in management information systems. Keywords: delone and mclean; information system success; LMS; SEM-PLS. Abstrak: Teknologi Informasi telah memengaruhi berbagai sektor, termasuk pendidikan. Learning Management System (LMS) dirancang untuk memfasilitasi dosen dan mahasiswa dalam mengakses kegiatan akademik seperti pembelajaran daring. Penelitian ini bertujuan untuk menganalisis efektivitas penggunaan Learning Management System (LMS) di perguruan tinggi di Indonesia. Analisis ini penting untuk menilai sejauh mana efektivitas penggunaan LMS oleh universitas-universitas di Indonesia, sehingga investasi dalam LMS dapat mem-berika n hasil yang optimal.Penelitian ini menggunakan model D&M IS Success Model dan metode PLS-SEM untuk mengevaluasi hubungan antara berbagai variabel, termasuk kuali-tas sistem, informasi, layanan, kepuasan pengguna, dan manfaat. Teknik simple random sampling digunakan untuk mengumpulkan data dari 170 perguruan tinggi di Indonesia. Penelitian ini menggunakan PLS-SEM untuk mengkaji variabel-variabel yang diamati, ter-masuk pengujian validitas dan reliabilitas, yang mencakup penilaian reliabilitas, validitas konvergen, dan validitas diskriminan. Hasil dari penelitian ini menunjukkan bahwa semua hipotesis diterima dengan nilai p di bawah 0,05. Temuan ini mendorong universitas untuk memberikan perhatian pada aspek kualitas sistem, informasi, dan layanan dalam penggunaan LMS guna meningkatkan kepuasan pengguna dan menciptakan persepsi posi-tif terhadap manfaatnya. Oleh karena itu, penelitian ini memberikan hasil yang signifikan bagi perguruan tinggi di Indonesia serta turut berkontribusi dalam pengembangan ilmu di bidang sistem informasi manajemen. Kata kunci: delone and mclean; kesuksesan sistem informasi; LMS; SEM-PLS